Central Line Associated Blood Stream Infection with Gram Negative Organisms: Clinical Features, Risk Factors and Mortality - Babar, Zaheer udin; Dodani, Sunil Kumar; Nasim, Asma; Kumar, Sanjay; Azmi, Maliha (Infectious Diseases Journal of Pakistan, 2022)
Background: Gram negative (GN) central line associated blood stream infection (CLABSI) has high mortality. Sindh Institute of Urology and Transplantation (SIUT) have a large dialysis unit and CLABSI is a major source of bacteremia. The aim of this study is to determine the clinical and microbiological characteristics, risk factors, antibiotics usage and mortality between CLABSI and non-CLABSI patients. Methods: It is a cross sectional study done at SIUT from May 2017 to March 2018. Patients >18 years, with GN bacteremia were included. Patients were divided into CLABSI and non-CLABSI groups. Age, ICU stay, mechanical ventilation, Pittsburgh (PITT) bacteremia score, comorbidities (diabetes mellitus, end stage renal diseases, hemodialysis, urinary catheters, recent surgery, stone disease etc.), clinical features (fever, hypotension, altered level of consciousness, leukocytosis, leucopenia, thrombocytopenia), appropriate antibiotic use were noted. Patients were followed till day 30. Results: Out of 137, 78 (56.9%) were CLABSI and 59 (43%) non-CLABSI. The significant risk factors for CLABSI were end stage renal disease (ESRD) [71.8% vs 15.3% p=<0.001 CI 14.14(5.97-33.56)] and hemodialysis [88.5% vs 30.5% p=<0.001 CI 17.46(7.18-42.46)]. Klebsiella species was commonly found in CLABSI (p=0.007) and Escherichia coli in non-CLABSI (p<0.001). Only 31% received appropriate empirical antibiotics. Mortality in CLABSI group was significantly associated with PITT bacteremia score (p=0.004), mechanical ventilation (p=0.007) and acute renal failure (p=0.008). Conclusion: ARF is major risk factor for CLABSI. Arterio-venous (AV) fistula formation should be expedited to prevent CLABSI associated bacteremia. Empirical antibiotics should be according to local antibiogram to avoid inappropriate use.